FRI0174 Spinal radiographic progression in early axial spa: 5-year data from the desir cohort. (12th June 2018) - Ramiro, S.; van der Heijde, D.; Sepriano, A.; van Lunteren, M.; Molto, A.; Feydy, A.; D' Agostino, M.A.; Loeuille, D.; Dougados, M.; Reijnierse, M.; Claudepièrre, P.
Abstract : Background: Spinal radiographic progression has been investigated in patients (pts) with r-axSpA, but not yet as thoroughly in early axSpA. Objectives: To analyse the progression of spinal radiographic damage in pts with early axSpA. Methods: Five-year follow-up data (baseline, 2 and 5 years) from the DESIR cohort, including pts with early axSpA, were used. Cervical and lumbar radiographs were centrally and independently scored by 3 readers (averaged scores), blind for chronological order and clinical characteristics, according to the mSASSS (0–72). Change scores for all available intervals were calculated. Pts were included if they had ≥1 mSASSS interval available (0–2 y, 2–5 y or 0–5 y). The development of new syndesmophytes (2 out of 3 readers) was calculated as a net change, i.e. subtracting the number of pts in whom an existing syndesmophyte ('noise') is no longer reported from those with a new syndesmophyte ('true progression'), divided by all pts. Two- and 5 year mSASSS progression and development of new syndesmophytes were assessed in each subgroup of pts according to the ASAS axSpA criteria and its arms at baseline (see figure 1). In addition, pts were grouped according to the fulfilment of mNYC and also to the presence of baseline syndesmophytes. Results: In total, 549 pts (mean age 34 (SD 9) years, 46% males, 63% fulfilling ASAS axSpA criteria, baseline mSASSS 0.46 (1.54)) were included. Thirty-eight pts (7%) showed syndesmophytes at baseline, 42% of which were ASAS axSpA criteria negative. Mean mSASSS progression was 0.15 (0.94) at 2 years and 0.42 (1.77) at 5 years. 18% of the pts fulfilling the ASAS axSpA criteria showed a 5 year positive mSASSS change (>0), compared to 30% in those not fulfilling the criteria (figure 1). 26% of the pts fulfilling the imaging arm had a positive change: highest positive change in MRI-mNYC+ (34%), followed by MRI+mNYC+(29%) and lastly MRI+mNYC- (23%). Mean mSASSS progression was highest in the mNYC +MRI + group (1.34 (3.98)). Eleven percent of the pts fulfilling only the clinical arm of the ASAS criteria had a positive change in mSASSS at 5 years, mean change of 0.13 (0.65). Pts with baseline syndesmophytes (across all subgroups) had the highest progression: 2.69 (5.02) mSASSS-units. At 5 years, 7% of all pts had a net change of any new syndesmophyte; this was 6% for ASAS+pts, 9% for ASAS-, 10% for pts fulfilling the imaging arm (18% for mNYC +MRI+) and 3% for pts fulfilling the clinical arm only. Seventeen percent of the mNYC +pts had a net change in new syndesmophytes as well as 42% of the pts with baseline syndesmophytes. The totals of some groups are higher than the sum of the subgroups due to missing data not allowing to classify patients into the subgroups. Conclusions: Spinal radiographic progression, though limited in early axSpA, can be captured already at 2 years of follow-up. Progression is higher in pts fulfilling the mNYC and also in pts with baseline syndesmophytes. Almost half of the pts with early axSpA with a syndesmophyte at baseline develop further syndesmophytes over 5 years. Disclosure of Interest: None declared